Tokyo ESP. 3 - Segawa, Hajime (Vertical, Inc, 2016)
"Rinka is targeted by The Professor's minions at school, with life-threatening consequences. Azuma wakes up, alone, on a deserted island, too far to help anyone. After we get a glimpse of The Professor's past and the true nature of the stone that creates the glowing fish, the terrorist gang's hijacking of the Diet building (by sending it flying through the skies) further enrages the government, which has already created a detention center for everyone with ESP. Th e Professor's ultimate act will have long-lasting repercussions, as the trap he set closes in on himself."--Cover.